Lipolysis defect in people with obesity who undergo metabolic surgery. (7th June 2022) - Rydén, Mikael; Andersson, Daniel P.; Kotopouli, Maria I.; Stenberg, Erik; Näslund, Erik; Thorell, Anders; Sørensen, Thorkild I. A.; Arner, Peter
Abstract: Objective: Cross‐sectional studies demonstrate that catecholamine stimulation of fat cell lipolysis is blunted in obesity. We investigated whether this defect persists after substantial weight loss has been induced by metabolic surgery, and whether it is related to the outcome. Design/Methods: Patients with obesity not able to successfully reduce body weight by conventional means ( n = 126) were investigated before and 5 years after Roux‐en‐Y gastric bypass surgery (RYGB). They were compared with propensity‐score matched subjects selected from a control group ( n = 1017), and with the entire group after adjustment for age, sex, body mass index (BMI), fat cell volume and other clinical parameters. Catecholamine‐stimulated lipolysis (glycerol release) was investigated in isolated fat cells using noradrenaline (natural hormone) or isoprenaline (synthetic beta‐adrenoceptor agonist). Results: Following RYGB, BMI was reduced from 39.9 (37.5–43.5) (median and interquartile range) to 29.5 (26.7–31.9) kg/m 2 ( p  < 0.0001). The post‐RYGB patients had about 50% lower lipolysis rates compared with the matched and total series of controls ( p  < 0.0005). Nordrenaline activation of lipolysis at baseline was associated with the RYGB effect; those with high lipolysis activation (upper tertile) lost 30%–45% more in body weight, BMI or fat mass than those with low (bottom tertile) initial lipolysis activation ( p < 0.0007). Conclusion: Patients with obesity requiring metabolic surgery have impaired ability of catecholamines to stimulate lipolysis, which remains despite long‐term normalization of body weight by RYGB. Furthermore, preoperative variations in the ability of catecholamines to activate lipolysis may predict the long‐term reduction in body weight and fat mass. Abstract :